α-Glucosidase, Angiotensin-converting Enzyme, and Acetylcholinesterase Inhibitory Activities of a Marine Red Alga Galaxaura oblongata - Duat, Kimnard Joseph Magsacay; Gelani, Chona de Guzman (Marine Science Department Diponegoro University, 2023)
Seaweeds have gained interest from the pharmaceutical industry due to their diverse secondary metabolites with potential applications in the prevention and treatment of lifestyle diseases. In spite of the abundance of seaweeds in the coastal area of Iligan Bay in the Philippines, there has been limited investigation into their pharmacological properties. Therefore, this study aimed to evaluate the in vitro α-glucosidase inhibition, angiotensin-converting enzyme (ACE) inhibition, and acetylcholinesterase (AChE) inhibition properties of various fractions obtained from the marine red alga Galaxaura oblongata. The methanol extract of G. oblongata was sequentially partitioned into hexane, dichloromethane, ethyl acetate, butanol, and methanol fractions. All assays were performed in vitro and microplate based. The results of α-glucosidase inhibition activity assay showed that the n-hexane fraction and dichloromethane fraction exhibited greater than 50% inhibitory activity at 200 ppm. Furthermore, ACE inhibition activity assay revealed that dichloromethane fraction, ethyl acetate fraction, and butanol fraction displayed ACE inhibition activity above 50% at 250 ppm. In addition, the hexane fraction, dichloromethane fraction, and ethyl acetate fraction demonstrated potent AChE inhibitory activity at 250 ppm. Overall, the findings show that G. oblongata has antidiabetic, anti-hypertensive, and neuroprotective potentials. This is the first report of the in vitro α-Glucosidase, ACE, and AChE inhibition activities of G. oblongata. Further investigation and purification of the highly potent fractions in each assay is highly suggested to identify and characterize the compounds responsible for the observed bioactivities, which could serve as possible leads for drug discovery efforts in the management of various lifestyle diseases.